Planning of district heating regions in Estonia - Volkova, Anna; Latõšov, Eduard; Lepiksaar, Kertu; Siirde, Andres (International Journal of Sustainable Energy Planning and Management, 2020)
It is quite evident that district heating networks will continue to be developed in order to complete their transition towards the 4th generation district heating by decreasing heat losses, increasing the share of renewable and waste heat sources, and integrating energy storage units and smart operating solutions. The significance of district heating in Estonia is very high, and developing this sector is very important for achieving climate and energy targets set by Estonia. Consumers play important role in the transition process, and for the purpose of informing and educating consumers, a district heating promo app has been implemented at the national level. One of the app’s modules shows consumers the energy mix that will be required to supply heat via district heating in the future, with all of the planned changes and different district heating regions taken into account. Measures and goals proposed in the Estonian National Development Plan of the Energy Sector until 2030, as well as all available heating strategies from various district heating regions have also been considered. The algorithm of the methodology takes into account possible changes in heating demand caused by increased energy efficiency of the building sector, heat loss reduction due to renovation of existing DH networks and possible reduction of DH temperature, as well as increase in the share of renewable energy sources and its impact on primary energy consumption and CO2 emissions in DH area. Scenarios show which fuel/primary energy mix is expected to be used for heat generation in the future (the data is given for each district heating region), as well as the amount of CO2 emissions. Several typical case studies are also provided.